Electrocorrosion and protection of metals : general approach with particular consideration to electrochemical plants - Riskin, Joseph (Elsevier, 2008)
Systematized data on electrocorrosion and protection of metals, especially in electrochemical plants allow using the book as a guide for corrosion engineers end researchers and for the personnel maintaining the equipment of all kinds of electrochemical plants to analyze the corrosion state of the metallic equipment and to prevent its electrocorrosion.